How executive incentive design affects risk-taking: a literature review - Kreilkamp, Niklas; Matanovic, Sascha; Schmidt, Maximilian; Wöhrmann, Arnt; Justus Liebig University Giessen (My University, 2023)
This paper presents a review of research regarding the effects of monetary executive incentives on risk-taking. More precisely, we investigate executives’ risk-taking (i) in response to the curvature (steepness, convexity, concavity) of the compensation function and (ii) with regard to reference points. Thereby, we refine and update common textbook knowledge. In this vein, we identify essential moderators at the personal, firm, or environmental level that can be used to assess the effectiveness of the incentive scheme in a specific context. Implications for incentive system design in practice and paths for future research are discussed.
Keywords: ddc:330